Effect of tonsillectomy in a child with obesity and obstructive sleep apnea: A case report and review of the literature - Di Filippo, Paola; Orlandi, Greta; Neri, Giampiero; Di Pillo, Sabrina; Chiarelli, Francesco; Rossi, Nadia; Attanasi, Marina (Frontiers in Pediatrics, 2023)
Obstructive sleep apnea (OSA) is an increasingly recognized disorder in children. Adenotonsillectomy is the primary surgical treatment for OSA in children with adenotonsillar hypertrophy. We present the case of an obese 4-year-old boy hospitalized for severe desaturation during sleep and severe adenotonsillar hypertrophy. Nasal steroid therapy proved ineffective with persistent symptoms. The polygraphy documented severe OSA with an apnea-hypopnea index (AHI) equal to 11. Tonsillectomy resulted in a prompt symptoms improvement and a substantial reduction of the AHI (2.2). In this case, tonsillectomy alone resulted effective for the treatment of OSA, despite obesity. We concluded that the presence of obesity should not postpone/exclude surgical treatment in preschool children, in whom adenotonsillar hypertrophy is the most important cause of OSA.